Karakteristik Pasien Rawat Inap Meninggal ≥48 Jam Dirawat: Pelatihan Penelitian bagi Perawat - Melati Fajarini; Sri Rahayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Nurses need data on patient mortality ≥48 hours of care, but nurses' skills to get these data are lacking. Nurses' lack of skills to produce scientific evidence is one of the obstacles to evidence-based practice (EBP). Research training for nurses is carried out to overcome obstacles and answer research problems. Research mentoring training was carried out for three days in June 2019 using the EBP stage. 10 nurses participated in this training. The training results reported that all nurses could plan, carry out, and report the results of the research. The research that nurses conducted was a retrospective study to collect data from 62 medical records of patients who died ≥48 hours of treatment in March-May 2019. The results of the nurse's study found that most of the patients were male (51.6%), aged over 45 years ( 66.1%), died with a medical diagnosis of Tuberculosis (27.4%), stroke (17.7%), HIV (12.9%), and with an indication of being hospitalized in the ICU (53.2%). Through training for three days, nurses can produce scientific evidence and provide recommendations for improving hospital management services. Essential research training is carried out in clinical areas to improve evidence-based practice, which in turn can improve the quality of care and health status of patients.